Isolation, Characterization And Identification Of A Fluoride Resistant Bacillus Species Isolate, H2 (Applied Biological Research, 2023)
Fluorine exists in the earth’s crust as fluorides (F) in fluorspar, fluorapatite and cryolite minerals (Ghosh et al., 2013). The F ion is toxic to the protoplasmic content of cell as it affects biochemical  contents when its level in drinking water exceeds 1.5 mg L-1(Annadurai et al., 2014). World Health  Organization and European Union have set the permissible limit of F in drinking water as 1.5 mg L-1,  while US Environment Protection Agency has set it as 4 mg L-1, and Indian Standard (IS) as 1.0 mg L-1(WHO, 2006; Edmunds et al., 2013). Fluoride reportedly has antimicrobial activity, and might  contribute to the anticaries activity by decreasing the growth and metabolism of microbes like  Streptococcus mutans (Hamilton, 1990), due to which F is extensively used in oral hygiene products  and even added to the municipal water supplies (Slayton et al., 2006). To avoid the ill effects of F,  different bacteria undergo changes in their genomes (Ying et al., 2017) and play a role in  bioaccumulation (Juwarkar and Yadav, 2010). Fluoride enters a bacterial cell at low pH as HF and  gets dissociated on exposure to neutral pH (Marquis et al., 2003). Fluoride ion once inside the bacterial  cells inhibit the important enzymes like enolase, F-ATPase and urease which can lead to the decrease  in bacterial growth and metabolism (Pandit et al., 2013). A F-resistant Pseudomonas aeruginosa achieved 22.1% removal of F (Chouhan et al., 2012), whereas strain RH5 removed 25.7% F from  growth medium (Mukherjee et al., 2017). Two F-resistant Bacillus strains KT201599 and KT201600  could survive at 2000-2500 µg sodium fluoride (NaF) mL-1and were able to remove F from media by  16.7 and 24.7%, respectively (Dutta et al., 2020). A F-tolerant halophilic Bacillus flexus NM25 could  tolerate 1,500 ppm F in brain-heart infusion agar medium and reduced F concentration up to 67.45%  (Pal et al., 2014) and Acinetobacter sp. could eliminate 57% F from the medium at specified  conditions (Shiva Shanker et al., 2020). Microorganisms behave variably to different F ion content in  media. Fluoride tolerant bacterial strains B. cereus FT1 and B. marisflavi FT2 showed higher F absorption efficiency in tryptone soya broth (Goutam et al., 2016). A F-resistant strain c180-2FR got  mutated for two glycolytic enzymes, pyruvate kinase and enolase (Ying Liao et al., 2018). Mutations  were also noted in promoter mutp which led to the upregulated expression of downstream F antiporters. However, decrease in enolase activity was not found associated with decrease in S.  mutans growth in NaF-enriched cultures (Mitsuhata et al., 2014). Fluoride contamination in ground  water is a major problem in some areas of Nalgonda district, Telangana (India) as the water intake  with high F leads to dental and skeletal fluorosis. To prevent these health issues, defluoridation of  water is done before consumption. The F-resistant wild strains with the ability to bioremediate F exist  in nature, which can be exploited and utilized. The present study was aimed to isolate and characterize a high F-resistant bacterium from ground water of Narketpally, Nalgonda district, Telangana (India).
Keywords: Isolation; Bacillus Species; Characterization